A model for non-volatile electronic memory devices with strongly correlated materials - Rozenberg, Marcelo Javier (2005)
The behavior of a model for non-volatile electronic memory devices with strongly correlated materials, was investigated. The domain structure assumed in this model is motivated from a rather universal aspect of strongly correlated perovskites such as the spatial inhomogeneity that occurs at the nanoscale. It is observed that the switching mechanism is related hysteresis in the I-V characteristics and that the hysteresis is itself related to a conjectured metal-insulator transition at the level of small domains. The results show that the domains that receive charge are subject to an 'effective doping' that may drive them across a boundary between two distinct electronic phases.